Ivermectin induces mitophagy in H9c2 cells via activation of the PINK1/Parkin pathway - JIA,Yanmin (2022)
Abstract Ivermectin (IVM), a remarkable broad-spectrum anthelmintic and insecticides, which also contributes to clinical application. However, IVM induction of cytotoxicity through mitophagy has not been consistently proven in vitro. Here we investigate the cytotoxic effects of ivermectin in mammalian nontarget cells. We have used cck-8 assay to evaluate the cell viability. The Fluorescence labeling was detected the occurrence of autophagy and mitophagy. The ATP bioluminescence detection kit was used to detect changes in intracellular ATP levels. In addition, the western blot assay was applied to reflect the expression of autophagy-related and mitophagy- related proteins. Cellular calcium concentration analysis was captured with a flow cytometer. We also used western blot to reveal expression of the lysosomal membrane protein Lamp2. The expression of lysosomal cathepsin mRNA was evaluated by RT-PCR. The cell viability was significantly diminished in H9c2 cells and the number of autophagosomes increases in a dose-dependent way, at the same time, LC3-II / I ratio was increased. We also found that the H9c2 cellular ATP level was decreased and observed the mPTP opening. The co-localization of mitochondria and lysosomes was detected, also, we found the concentration of Ca2+, the expression of Lamp 2 and mRNA expression levels of Cathepsin B and Cathepsin L significantly increased in a dose-dependent way in H9c2 cells. Finally, the results of expression of PINK1 and Parkin protein increased simultaneously in H9c2 cells. IVM induced mitophagy in H9c2 cells via PINK1/Parkin signaling.